Dietary intake and anthropometric changes during the rehabilitation of some severely malnourished male preschoolers an exploratory study - Manalo, Ruth Agnes B. Lacuesta; Florencio, Cecilia A. (1987)
Eight severly malnourished male pre-schoolers underwent nutrition rehabilitation at the University Health Service nutreward. The children's socio-economic background was studied, changes in the volume of food, Calorie and protein intake, as well as physical growth was measured upon admission, at various points during the rehabilitation, and at the end of rehabilitation. The Calorie and protein intake of the children were compared with the Ministry of Health (MOH) recommendations and the length of time needed to meet discharge criteria were determined. Results of the study showed that the malnourished children came from families with low income, poorly educated parents who are migrants from the provinces, and mean household size of 5.5 with two pre-schoolers. Intra- and inter-individual variations in food and nutrient intake were observed throughout the rehabilitation period. The mean Calorie intake throughout the rehabilitation period was 112 Cal/KDBW and 165 Cal/KABW with protein providing 12 to 15% of total Calories. The mean Calorie intake at level 9 was not significantly different from the MOH recommendation of 50 Cal/KDBW. The mean intake at level 8 was significantly higher than the 50 and 75 Cal/ KDBW MOH recommendation. The mean intakes from level 7 to 5 were significantly higher than the MOH recommendations of 50, 75, and 100 Cal/ KDBW. The 150 Cal/ KDBW recommendation was significantly higher than the means in all the nutritional levels. The mean protein intake per level was not significantly different from the 4 gm/ KDBW MOH recommendation. The 2 and 6 gm/ KDBW recommendation were significantly different from the mean intake of the subjects throughout the rehabilitation period. Weight, height, and mid-upper arm circumference measurements significantly increased during rehabilitation. The additional 10% and 20% of DBW MOH discharge criteria were met after 3.7 and 6.1 weeks respectively, while the 76% weight-for-age discharge criteria was met after 9.3 weeks. The findings suggest that the education session for parents of malnourished children in nutreward should include topics that go beyond foods and nutrition such as income generation. The data also show that Calorie recommendations per KDBW per day may be as follows:80-90 at level 9, 90-200 at level 8, and 110-120 from level 7 to 4. Weight-for-age and weight-for-height can be used to assess physical changes. Due to the exploratory nature of this study, one that involves more children should be made to validate these findings.
Computer print-out (photocopy).
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: Malnutrition in children -- Philippines; Children -- Philippines -- Nutrition